Pemberdayaan Buruh Perempuan dalam Proses Produksi Batu Kapur - Rohimi, Rohimi (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2019)
This article discusses how the process of limestone production, and in the process there are things that are so interesting for researchers to observe, namely when the production of limestone is not easy, but extensively has a majority of female workers. Even though in the process of limestone production the workers or laborers must work with heavy goods such as amer, stone, wood. So that this study discusses more intensively related to how to give priority to empowering female lime workers as creatures that are far weaker than men. And this research was conducted in Mangkung Village, West Praya District, Central Lombok Regency. Because for researchers there is a suitable object to continue the vision to provide a new understanding of its findings related of the female workers in the scope of the process of producing limestone.